Enhanced PET processing with organophosphorus additive: Flame retardant products with added-value for recycling. (February 2019) - Gooneie, Ali; Simonetti, Pietro; Salmeia, Khalifah A.; Gaan, Sabyasachi; Hufenus, Rudolf; Heuberger, Manfred P.
Abstract: At elevated temperatures, polyethylene terephthalate (PET) is known to undergo a cascade of interconnected chemical reactions, in particular oxidative crosslinking, which can lead to severe limitations in processability, product properties, and recyclability. To control such undesired reactions, a newly synthesized phosphorus-based additive with promising flame retardant properties (T. Stelzig et al. Dopo-Based Hybrid Flame Retardants. EP2921498 (A1), 2015), by the chemical name 6-((1-oxido-2, 6, 7-trioxa-1-phosphabicyclo[2.2.2]octan-4-yl)methoxy)dibenzo[c, e][1, 2]oxaphosphinine 6-oxide (DOPO-PEPA, or simply DP), was added to PET in different concentrations. To assess the miscibility of DP and PET at the nanoscale, a multiscale simulation scheme was developed by combining molecular dynamics and dissipative particle dynamics. DP showed a prominent inter-chain lubrication effect in PET in extrusion experiments. To replicate the heating cycles during repeated recycling, the thermal stability of PET melts was assessed on extended timescales using rheological measurements. Time-resolved frequency sweep experiments were conducted with or without the novel DP additive, under air and nitrogen atmospheres. By combining various chemical analysis techniques, a chemical stabilizing mechanism could be proposed that describes how the DP molecule intervenes with the degenerative chemical reactions of PET chains in the melt processing phase. The proposed mechanism outlines trace-release from DP involving the formation of phosphorus radicals including DOPO, PEPA, and PO . Such radicals scavenge the oxygen radicals from air and can thus protect the linearity of PET chains. The results underline the synergistic effects of DP on the processing of high performance PET. Together with flame retardancy of the original product, the environmental-friendly DP chemically-protects and lubricates PET during subsequent recycling of the waste. Graphical abstract: Image 1 Highlights: DOPO-PEPA is a multifunctional, non-toxic, and eco-friendly additive. DOPO-PEPA acts as a molecular lubricant in PET melt. PET melt stability at elevated temperatures is improved by the addition of DOPO-PEPA. Thermo-oxidative crosslinking is controlled in PET melt at elevated temperatures. The recyclability of PET is improved due to synergistic behavior of DOPO-PEPA.